Health consequences of Typhoon Haiyan in the Eastern Visayas region using a syndromic surveillance database - Salazar, Miguel Antonio; Winkler, Volker (PLoS Currents, 2017)
Introduction: Typhoon Haiyan was the strongest storm recorded in Philippine history. Surveillance in Post Extreme Emergencies and Disasters (SPEED) was activated during the typhoon response. This study analyzes the health impact of different diseases during different timeframes post-disaster during Typhoon Haiyan in 2013 using a syndromic surveillance database., Methods: SPEED reports medical consultations based on 21 syndromes covering a range of conditions from three syndrome groups: communicable diseases, injuries, and non-communicable diseases (NCDs). We analyzed consultation rates for 150 days post-disaster by syndrome, syndrome group, time period, and health facility type for adults as well as for children under the age of five., Results: Communicable diseases had the highest consultation rates followed by similar rates for both injuries and NCDs. While communicable diseases were the predominant syndrome group for children, wounds and hypertension were common syndromes observed in adults. Village health centers had the most consultations amongst health facilities, but also showed the highest variability., Discussion: Children were more vulnerable to communicable diseases compared to adults. Community health centers showing consistently high consultation rates point out a need for their prioritization. The predominance of primary care conditions requires disaster managers to focus on basic health care and public health measures in community health centers that target the young, elderly and impoverished appropriate to the time period.